Attitudes of Healthcare Professionals and General Population Toward Vaccines and the Intention to Be Vaccinated Against COVID-19 in Spain - Iguacel, Isabel; Luna Maldonado, Aurelio; Luna Ruiz-Cabello, Aurelio; Samatán, Eva; Alarcón, Judith; Ángeles Orte, María; Santodomingo Mateos, Silvia; Martínez-Jarreta, Begoña (Frontiers in Public Health, 2021)
Background: To achieve herd immunity, the acceptance of the COVID-19 vaccine by the population, especially healthcare professionals, plays a key role. The objective of the present paper is to address the differences in attitudes among Spanish healthcare professionals compared with the general population regarding COVID-19 vaccination. Methods: This cross-sectional study included data from 2,136 adults (n = 664 healthcare professionals) from an online survey conducted from May 6 to June 9, 2021. The Vaccination attitudes examination scale was used to measure the negative attitudes toward vaccines. Four subscales: mistrust of vaccine benefit, worries about the unforeseen future effect, concerns about commercial profiteering, and preference for natural immunity were calculated. Generalized linear mixed models were conducted to study these associations. Results: Between 10.2 and 22.6% of the subjects showed high levels of negative attitudes toward vaccines. However, only 1.5% of our sample (2.1% among healthcare professionals) refused to get the COVID-19 vaccine when it was offered because they chose otherwise. Retired people showed the lowest concerns and the highest trust in vaccines. No statistically significant effects were found between working in a healthcare field and having higher positive attitudes toward vaccines. Conclusion: Low levels of rejection against the COVID-19 vaccine were identified in the present sample. However, despite being at a higher risk, health care professionals did not show higher positive attitudes toward vaccines. Furthermore, refusal percentage to vaccination was higher among healthcare professionals compared with non-healthcare professionals. Developing a strategy to increase positive attitudes against the COVID-19 vaccine should be an objective for public health policy.